Perspective-Taking Interventions for Intergenerational Caregivers of Alzheimer's Diseases: A Randomized Controlled Trial. (March 2020) - Au, Alma; Lai, Daniel W. L.; Biggs, Simon; Cheng, Sheung-Tak; Haapala-Biggs, Irja; Chow, Amy; Gallagher-Thompson, Dolores
Purpose: The present study examined the effects of perspective-taking (PT) intervention in the context of intergenerational caregiving. Method: Seventy-two adult child caregivers of persons living with Alzheimer's disease (AD) were randomized into two 8-week interventions: (1) connecting through caregiving (CTC: 37 participants) with intergenerational PT reappraisals and (2) basic skill building (BSB: 35 participants). The CTC intervention focused on PT reappraisals aiming to promote balance between self-care and caring of others: (1) connecting with self through enhancing self-awareness, (2) connecting with the care recipient through empathetic understanding, and (3) connecting with others who can help. Results: As compared to the BSB group, the CTC group reported significantly higher increase in the level of life satisfaction and also greater reductions in depressive symptoms and burden. PT was found to mediate between intervention effects and change in life satisfaction. Discussion: The results provided evidence for the efficacy of the CTC program in enhancing the well-being of AD caregivers.